Core-Substituted Naphthalene-Diimides (cNDI) and Related Derivatives: Versatile Scaffold for Supramolecular Assembly and Functional Materials - Anurag Mukherjee; Suhrit Ghosh (Organic Materials, 2021)
Abstract Naphthalene-diimide (NDI)-derived building blocks have been explored extensively for supramolecular assembly as they exhibit attractive photophysical properties, suitable for applications in organic optoelectronics. Core-substituted derivatives of the NDI chromophore (cNDI) differ significantly from the parent NDI dye in terms of optical and redox properties. Adequate molecular engineering opportunities and substitution-dependent tunable optoelectronic properties make cNDI derivatives highly promising candidates for supramolecular assembly and functional materials. This short review discusses recent development in the area of functional supramolecular assemblies based on cNDIs and related molecules. Table of contents 1. Introduction 2. General Supramolecular Assemblies of cNDI Derivatives 3. cNDI-Based Chiral Supramolecular Assemblies and Functional Materials 4. Controlled Supramolecular Polymerization with cNDI Derivatives 5. Dimeric Naphthalimide-Based Building Blocks 6. Conclusions and Outlook